Symptomatic presentation influences outcomes in pediatric restrictive cardiomyopathy - Lorenzo, Melissa; Lynch, Aine; Ashkanase, Jenna; Fazari, Linda; George, Kristen; Arathoon, Katelyn; Minn, Sunghoon; Nicolson, Dawn; Jeewa, Aamir; Jean-St-Michel, Emilie (Frontiers in Pediatrics, 2023)
Children with restrictive cardiomyopathy (RCM) traditionally have a poor prognosis, with most patients either dying or requiring heart transplantation within 2 years of diagnosis. The development of symptoms in RCM suggests advanced disease. However, as screening practices evolve and lead to diagnosis of early disease, identifying appropriate timing of transplant listing becomes increasingly important. In this context we compared outcomes of children with RCM presenting with clinical symptoms to those asymptomatic at initial presentation.Methods: This retrospective cohort study included 25 patients with RCM presenting to a quaternary care center between 2001-2018. Times to transplantation, death, and a composite outcome of adverse cardiac events (CPR, cardioversion, inotropic support, mechanical ventilation, mechanical support, or heart transplant) were compared between those symptomatic and asymptomatic at presentation.At 2 years following diagnosis, patients asymptomatic at presentation had a significantly better transplant-free survival at 57% compared to 17% for symptomatic patients (p=0.03). Those asymptomatic at diagnosis also had significantly improved cardiac event-free survival at 71% compared to symptomatic patients at 25% (p=0.01). In multivariable analysis, cardiac symptoms at presentation remained an independent risk factor for heart-transplant or death (hazard ratio 5.17 (1.28-20.85), p=0.02).Patients with RCM who are symptomatic at time of diagnosis have significantly worse transplant free survival and cardiac event free survival. Given current practice variability in timing of transplant listing, the presence of any cardiac symptoms is an important negative prognostic marker and should prompt urgent transplant listing.